2021
DOI: 10.18502/ijph.v50i5.6105
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Roles in Nursing Disaster Model: A Systematic Scoping Review

Abstract: Background: Nurses have a continuous presence and crucial role in response to disasters. During disasters, nurses apply specific knowledge and skills to minimize victims’ health and life-threatening risks. Nurses’ roles in crisis are not clearly stated in resources. Thus, this study aimed to explore nurses’ role in the nursing disaster model. Methods: A scoping review was conducted using Joanna Briggs Institute framework. The review considered primary research and reviewed literature from following datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…Disaster nursing education programs, including the program proposed in this study, focus mainly on the disaster response & ICN, 2009) has noted nursing to be the most important role during the disaster response stage, during which the preservation of life and health of victims is prioritized. Nurses are the frontline healthcare providers in most disaster response efforts (Firouzkouhi et al, 2021;World Health Organization & ICN, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Disaster nursing education programs, including the program proposed in this study, focus mainly on the disaster response & ICN, 2009) has noted nursing to be the most important role during the disaster response stage, during which the preservation of life and health of victims is prioritized. Nurses are the frontline healthcare providers in most disaster response efforts (Firouzkouhi et al, 2021;World Health Organization & ICN, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A review showed that nurses play different roles in crises that need the combination of knowledge, perception and judgement, with cognitive, psychomotor and interpersonal skills [ 26 ]. According to the results of this study, to improve the quality of care for the patients, nurses should be aware of their roles in crises.…”
Section: Discussionmentioning
confidence: 99%
“…During disasters, the social standing of nurses elevates due to their crucial role in response and care. Their continuous presence and application of specialized knowledge and skills to mitigate health risks establish them as dependable responders [ 31 ]. As a result, their dedication, compassion, and unwavering commitment to patient care, even in the face of challenging circumstances, can enhance the public perception of them.…”
Section: Discussionmentioning
confidence: 99%